Airway Stents in Interventional Pulmonology - Sami I. Bashour; Donald R. Lazarus (MDPI AG, 2024)
Airway stents, first developed in the 1980s, have become fundamental in managing a multitude of airway pathologies and complications within the field of interventional pulmonology. The primary function of an airway stent is to re-establish airway patency and integrity when obstruction, stenosis, anastomotic dehiscence, or fistulae develop as a result of various malignant or benign conditions. Nevertheless, airway stents are foreign bodies that can result in complications. In this review article, we will discuss airway stents and their ongoing role in the management of several malignant and benign diseases. We will describe indications for airway stenting and review the elements that must be taken into consideration for optimal patient and stent selection. Given the prevalence of data regarding therapeutic bronchoscopy and airway stenting in malignant airway obstruction, much of the discussion in this review will focus on stent placement for that indication. We will also review the data as it pertains to safety, efficacy, and complications after stent placement, and conclude with a discussion of the future applications and research avenues related to airway stents.